How properties of urban greenspaces shape well-being across age groups: A qualitative study - Rebecca Reece; Lewis Elliott; Isabelle Bray; Anna Bornioli (Wellbeing, Space and Society)
The prevalence of poor mental health among younger and older generations is rising. Urban greenspaces (UGS) can provide well-being benefits and are used by all ages, so it is important that these spaces provide benefits across the life course. So far, studies tend to focus on one age group and lack focus on properties of these spaces which shape well-being across generations. Our aim was to explore what properties of UGS can shape well-being across age groups and to what extent are UGS for social interactions across age groups. Qualitative semi-structured interviews were conducted online with 20 participants in four age groups: adolescents, young adults, adults, and older adults. Interviewees were asked about visits to UGS, preferences for multi-sensory components, and how spaces shape their well-being. Using thematic analysis, four themes were identified which were common across all age groups: UGS can provide a sense of escape; there are practical needs surrounding access and contact with UGS; being a space to share with other users; and the importance of seasonal multi-sensory components. Whilst findings showed that there are properties of UGS which are valued across multiple ages, differences were also revealed regarding interactions across ages. By researching qualitatively across ages, the complex similarities and differences between ages can be understood. Future research should also explore interactions between age groups as well as the views of non-users of UGS and their reasons for not visiting UGS.